Air Pollution-related Stroke in Guadalajara. A Call to Action (Ictus, 2024)
Editorial on "Air Pollution-related Stroke in Guadalajara. A Call to Action" presented in volume 5 number 1 of 2024 of ICTUS.
Keywords: Ischemic Stroke; Hemorrhagic stroke; Air-pollution